(untitled) (Libya Journal of Geographical Studies, 2025)
The establishment of wastewater treatment plants is one of the most important and effective means for the safe and beneficial disposal of wastewater, ensuring public safety and avoiding unacceptable environmental risks. In most cities in Libya, including the study area, it is observed that wastewater discharged from households and institutions—regardless of its source—is disposed of directly into the sea without treatment, thus posing a serious threat to the environment and public health. This research aims to identify the optimal location for establishing a wastewater treatment plant in the Al-Khoms area using Geographic Information Systems (GIS) and Remote Sensing—key tools in this field that are widely relied upon for planning and decision-making. The study adopted an applied and analytical methodology based on the visual representation of scientific data, including several paper maps and satellite imagery. After extracting and classifying the relevant layers, the Weighted Overlay Model was applied. This process resulted in the production of a digital map through which the optimal site for constructing a wastewater treatment plant in the region was identified. The outcome supports well-informed decisions regarding suitable geographic locations for various environmental projects in the area.